Plant taxonomy and nomenclature - Jager, Siegfried (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2003)
Scientific classification of organisms is a very important task but also an extremely difficult one. Taxonomic analyses allow the reconstruction of a pedigree of plants and also the degree of relationship to each other. The paper describes basic rules of plant taxonomy together with systematics of higher plants indicating families of special aerobiological interest.